MEMINIMALISIR KONFLIK SOSIAL BERAGAMA DI INDONESIA - Akhmad Syarief Kurniawan (Postgraduate State Islamic Institute (IAIN) Metro, 2015)
Indonesia is an area that is unstable and prone to conflict. Confronted in a variety of social problems such as high levels of poverty, unemployment, social inequality, social tension, and political instability, as well as the political institutions of democracy are not yet effective, the areas in Indonesia holds the potential conflict which at times can be sticking to the surface into a violent conflict open. The violent conflict in the past, such as occurred in Maluku, North Maluku, Poso, West Kalimantan, Aceh, Papua, bringing the impact of conflict with the social damage and casualties is not small. While, though most areas of conflict in Indonesia has now entered a post-conflict situation, the potential for conflicts (latent conflict) is still very high. Thus potential conflicts at times can turn into open violent conflict, when efforts prevention conflict and peace-building have not worked effectively. The high pluralism in Indonesia create potential conflicts of Indonesia is also high. Potential friction and misunderstandings are also high. Both conflicts on a small scale or a large scale. In a small scale, the conflict is reflected in the communication not connected or not running as it should, causing a sense of hurt, angry, frustrated, disappointed, irritated, confused, wondering, and others. Meanwhile, large-scale conflict embodied in, for example, social unrest, multi-cultural chaos, hostility between races, ethnicities and religions, and others. One of the factors that encourage the appearance of a conflict-prone society is a problem related to the elements Tribe, Religion, Race, and groups (SARA). Especially religious differences, common be driving the emergence of tensions in society, for example, issues related to the establishment of a means of worship, religious activities and the implementation of practical political problems.